2009
DOI: 10.4314/ejesm.v2i2.45919
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution and Accessibility of Health Facilities in Akwa Ibom State, Nigeria.

Abstract: Halting the spread of preventable diseases is one of the Millennium Development Goals (MDGs) with 2015 as target period for achievement. The attainment of this goal is a function of the spatial pattern of distribution of healthcare facilities and a measure of the degree of accessibility to healthcare services. This paper therefore analyzed the spatial patterns of healthcare facilities in Akwa Ibom State against the philosophy of achieving the MDGs in the health sector. Data from official records of government … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Moreover, many studies show that there is a positive correlation between the availability of health resources and health outcomes represented by life expectancy and mortality rates (6,7). Therefore, equitable distribution of health resources in developing countries is of paramount importance, as many of these countries face severe shortages in physical and human resources to provide essential health care services (8,9). In Sudan, inequitable regional distribution of wealth and resources has been the leading driver of political conflicts and violence since its independence in 1956 (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many studies show that there is a positive correlation between the availability of health resources and health outcomes represented by life expectancy and mortality rates (6,7). Therefore, equitable distribution of health resources in developing countries is of paramount importance, as many of these countries face severe shortages in physical and human resources to provide essential health care services (8,9). In Sudan, inequitable regional distribution of wealth and resources has been the leading driver of political conflicts and violence since its independence in 1956 (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The population distribution by district/municipalities was displayed in the 37501.0000001-78907.000000 (6) 78907.000001-102574.000000 (9) 102574.000001-136483.000000 (7) 136483.000001-183727.000000 340 Miles 0 10 20 OALibJ | DOI:10.4236/oalib.1102956 5 August 2016 | Volume 3 | e2956 Figure 2 displays the breakdown of the Eastern Region into its 26 administrative districts by population. The legend shown at the top left corner of the map shows the population in ranges arranged from the highest to the lowest, the strength of the color shade corresponds to how high or low the population is.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately health care services is not equally accessible to all people and continues to be a major barrier to achieving the goal of health care for all and sundry [6]. Atser and Akpan (2009) reported that variation in distribution of facilities is crucial especially in rural areas where there are problems of limited facilities and low mobility of health personnel [7]. Results from a study in Ondo State showed that healthcare facilities in the state were unevenly distributed, hence hampering health development at the grassroots [8].…”
Section: Introductionmentioning
confidence: 99%
“…According to Atser and Akpan (2009), within developing societies where there are problems with limited facilities and low personal mobility (accessibility), inequality in facilities' distribution is of crucial importance. Accessibility in this context has a spatial theme and signifies the ease with which potential healthcare seekers get to the health facilities unhindered.…”
Section: Introductionmentioning
confidence: 99%